2021
DOI: 10.1002/aocs.12521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AOT reverse micelle extraction on structure and emulsifying properties of soybean protein

Abstract: The present study aimed to investigate the forward and backward extraction efficiency, structure, and emulsifying properties of soybean proteins obtained through bis (2-ethylhexyl) sulfosuccinate sodium salt (AOT) reverse micelle, as well as their relationship. The results showed that the extraction efficiency was the highest with the forward extraction time of 25 min, pH of 3.0, temperature of 45 C, KCl concentration of 0.0 mol L À1 , and the backward extraction time of 10 min, pH of 4.0, temperature of 30 C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This might be because a large amount of lye in the alkaline extraction process caused damage to the secondary structure of tea protein, while the secondary structure of tea protein was preserved integrally due to the protective effect of the ‘pool’ in the reverse microemulsion 44 . Some studies have also confirmed that the protein extracted by reverse microemulsion has a more stable secondary structure 44,48,49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because a large amount of lye in the alkaline extraction process caused damage to the secondary structure of tea protein, while the secondary structure of tea protein was preserved integrally due to the protective effect of the ‘pool’ in the reverse microemulsion 44 . Some studies have also confirmed that the protein extracted by reverse microemulsion has a more stable secondary structure 44,48,49 …”
Section: Resultsmentioning
confidence: 99%
“…44 Some studies have also confirmed that the protein extracted by reverse microemulsion has a more stable secondary structure. 44,48,49 Analysis and evaluation of amino acid composition Amino acid composition and content of tea protein extracted by the two methods are shown in Table 4.…”
Section: Verification Testmentioning
confidence: 99%
“…Depending on the moisture content, the extrusion can be categorized into low-moisture extrusion (<30%) and high-moisture extrusion (50%) [23]. The former is widely applied in non-meat products, such as the production of textured vegetable protein (TVP), where a high protein content in the raw material is not a prerequisite [24,25]. TVP serves as an ingredient in various food applications, including taco fillings and pizzas, owing to its texture and protein content, making it an ideal substitute for animal-derived proteins [4].…”
Section: Physical Assisted Methodsmentioning
confidence: 99%
“…[ 20 , 21 ]. RMs extraction has been used to purify plant proteins such as soy protein [ 22 ], peanut protein [ 23 ], walnut protein [ 24 ], bromelain [ 25 ], and papain [ 26 ]. Therefore, RMs extraction has a high potential for downstream processing, especially in food science.…”
Section: Introductionmentioning
confidence: 99%